PENGERTIAN INTERFACE MANAGEMENT DALAM ORGANISASI PROYEK KONSTRUKSI - Ipak Neneng Mardiah Bukit (Jurnal Teknik Sipil Unaya, 2017)
Construction project organization is a very complex system that is involving many parties. To ensure the organization work properly, therefore a good management system is required. This is important to ensure all individual work in a pleasant working environment. The goal of the system is to avoid friction among people in the project site. Interface management (IM) becomes significant in the project organization. IM is a management system developed thus all the stakeholders in a project or every party in a process can work together, can communicate and be responsible to their works during the implementation process of construction. IM is project manager’s job in management project. This paper will discuss IM definition, interfaces problems and IM procedures that should be implemented in order to achieve project success. The result of this discussion is a project will be efficiently generated if the project manager implements IM from the beginning of the project implementation.